Malcolm X : by any means necessary - Myers, Walter Dean, 1937-2014 (New York: Scholastic Focus, 2020)
Few men in American history are as controversial as Malcolm X. In this provocative biography, Myers, winner of a Newbery Honor and four-time Coretta Scott King Award winner, presents a forthright portrait of a complex man whose life reflected the major events of our times.
Introduction: A man called Malcolm -- Father -- Son -- Creating a new image -- Detroit Red -- Nation of Islam -- Message -- Freedom and a new name -- Minister Malcolm -- In the public eye -- Man named Martin -- March on Washington -- Split with Elijah Muhammad -- Malcolm's Hajj -- New message -- Word on the street -- Assassination -- Son is buried -- Who killed Malcolm? -- Legacy.
Includes bibliographical references (pages 195-196) and index.
Accelerated Reader AR
Coretta Scott King Honor, author, 1994.
Keywords: X, Malcolm, -- 1925-1965 -- Juvenile literature; X, Malcolm, -- 1925-1965.; X, Malcolm; X, Malcolm, -- 1925-1965.; X, Malcolm, -- 1925-1965.; Black Muslims -- Biography -- Juvenile literature; African Americans -- Biography -- Juvenile literature; Black Muslims; African Americans -- Biography; Black Muslims -- Biographies -- Ouvrages pour la jeunesse; v; Black Muslims -- Biography; African Americans -- Biography; African Americans; Black Muslims; Black Muslims -- Biography; Blacks -- Biography; Biography; Biographies; Juvenile works; Biographies; Biographies